2020
DOI: 10.3389/fimmu.2020.02015
|View full text |Cite
|
Sign up to set email alerts
|

Trichinella spiralis Thioredoxin Peroxidase 2 Regulates Protective Th2 Immune Response in Mice by Directly Inducing Alternatively Activated Macrophages

Abstract: TsTPX2 Regulates Th2 Immune Response trichinosis. Our study showed that TsTPX2 would be at least one of the molecules to switch macrophages into the M2 phenotype during T. spiralis infection, which provides a new therapeutic approach to various inflammatory disorders like allergies or autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“… 96 Thioredoxin peroxidase-2 of Trichinella spiralis can induce alternative activation of macrophages and differentiation of naïve T cells into Th2 cells in vitro. 97 Cystatin of Trichinella spiralis can inhibit the Th1-type immune response by inducing production of IL-4 and Treg cells in TNBS-induced colitis. 98 Peroxiredoxin secreted by Schistosoma mansoni or Fasciola hepatica can induce the alternative activation of macrophages and the activation of naive T cells to secrete IL-4, IL-5 and IL-13.…”
Section: The Immunoregulatory Mechanisms Of Identified Helminth-derived Moleculesmentioning
confidence: 99%
“… 96 Thioredoxin peroxidase-2 of Trichinella spiralis can induce alternative activation of macrophages and differentiation of naïve T cells into Th2 cells in vitro. 97 Cystatin of Trichinella spiralis can inhibit the Th1-type immune response by inducing production of IL-4 and Treg cells in TNBS-induced colitis. 98 Peroxiredoxin secreted by Schistosoma mansoni or Fasciola hepatica can induce the alternative activation of macrophages and the activation of naive T cells to secrete IL-4, IL-5 and IL-13.…”
Section: The Immunoregulatory Mechanisms Of Identified Helminth-derived Moleculesmentioning
confidence: 99%
“…As an example of in vitro analyses, Jin et al (2020b) investigated the immunomodulatory effect of T. spiralis muscle larvae thioredoxin peroxidase-2 (TsTPX2) in the regulation of Th2 response. They found that rTsTPX2 could directly drive peritoneal macrophages to the AAM phenotype.…”
Section: How Does Trichinella Tame the Host Immune...mentioning
confidence: 99%
“…The immunomodulatory effect of T. spiralis thioredoxin peroxidase-2 (TsTPX2), a protein derived from T. spiralis muscle larvae ES products was investigated by Jin et al (2020b) . They stated that TsTPX2 could suppress Th1 immune responses and promoting Th2 cytokines, IL-4 and IL-10 via polarization of macrophages into the AAM phenotype.…”
Section: Trichinella -Derived Molecules: a Panacea For Moder...mentioning
confidence: 99%
“…Some of these proteins have been studied for immunity in other parasitic worms. For example, the Trichinella spiralis ES product thioredoxin peroxidase-2 could induce macrophages towards an M2-like phenotype, both in vivo and in vitro, and CD4 + T cells increased in number after immunization of mice with rTsTPX2 and this mediated the expulsion of worm from the host to protect them, thus suggesting TsTPX2 was a potential vaccine candidate against trichinosis [30]. Also, thioredoxin peroxidase was signi cantly recognized by melioidosis-positive sera in cysticercus stage, for which strong immunogenic properties rendered it an anticipated vaccine target [31].…”
Section: Discussionmentioning
confidence: 99%